2019
DOI: 10.12688/f1000research.17228.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding necrotizing enterocolitis

Abstract: Necrotizing enterocolitis is a devastating intestinal disease affecting preterm infants. In spite of ongoing research and advancement in neonatal care, mortality remains high, especially in infants with advanced disease. The mechanism of disease development, the progression of intestinal injury, and management remain areas of ongoing research and controversy. In this review, we examine our current understanding of the disease, its epidemiology, the risk factors associated with the development of the disease, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 79 publications
3
100
0
7
Order By: Relevance
“…Moreover, antenatal steroids are associated with a decrease in incidence of PDA, since these attenuate the sensitivity of the DA to PGE 2 and increase the PGE 2 catabolism. Robust evidence exists on the presence of an association between low GA and development of NEC [17]. In the current study, we identified GA as an independent predictor for the development of sNEC.…”
Section: Perinatal Variablesmentioning
confidence: 50%
“…Moreover, antenatal steroids are associated with a decrease in incidence of PDA, since these attenuate the sensitivity of the DA to PGE 2 and increase the PGE 2 catabolism. Robust evidence exists on the presence of an association between low GA and development of NEC [17]. In the current study, we identified GA as an independent predictor for the development of sNEC.…”
Section: Perinatal Variablesmentioning
confidence: 50%
“…Other morbidities in the neonatal intensive care unit (NICU) such as necrotizing enterocolitis (NEC) also have high mortality rates and have been associated with prolonged antibiotic exposure. 10,11 . Nevertheless, antibiotics remain the most commonly prescribed medication in the NICU 12,13 .…”
Section: Mainmentioning
confidence: 99%
“…NEC involves derangement of intestinal microcirculation that leads to poor blood flow, which may induce an inflammatory cascade, resulting in intestinal injury. 20 In this study, we hypothesized that in NEC, the intestinal injury leads to release of mtDNA from the necrotic intestinal epithelial cells. The increased levels of mtDNA could enhance the inflammatory injury trough activation of TLR-9 receptors while mtDNA released in the circulation triggers injury in remote organs.…”
Section: Discussionmentioning
confidence: 99%